SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) PADA PEKERJAAN PEMBANGUNAN GEDUNG GIZI RSUD Dr. KANUJOSO DJATIWIBOWO BALIKPAPAN - YUSNI, MUHAMMAD (KURVA S JURNAL MAHASISWA, 2014)
Health and safety is the Occupational Health and Safety with the sense of giving protection to any person who is in the workplace, which is associated with the transfer of raw materials, the use of work equipment construction, production processes and the environment around the workplace.Hospital Dr. Kanujoso Djatiwibowo Balikpapan is one of the Regional General Hospital Class B. Based on the Technical Building Code standards Hospital Grade B then made Nutrition Building Hospital Dr. Kanujoso Djatiwibowo Balikpapan aimed as facilities in the process of handling food and beverages. The building will be built with the Nutrition Hospital Dr. Kanujoso Djatiwibowo Balikpapan it is very important to note that occupational health and safety issues (K3) in the building construction phase. Because the problem of occupational safety and health (K3) is generally in Indonesia is often overlooked, as shown by the high number of work accidents.From the analysis and observations, the results obtained, among others, include the potential of danger and risk level of work, the Implementation Plan implemented K3, K3 and management systems that exist in the location of work.